[PP.09.17] REPRODUCIBILITY OF THE EVALUATION OF THE WALL TO LUMEN RATIO OF RETINAL ARTERIOLES WITH TWO DIFFERENT NON-INVASIVE APPROACHES: SCANNING LASER-DOPPLER FLOWMETRY AND ADAPTIVE OPTICS. (September 2017) - De Ciuceis, C.; Coschignano, M.A.; Caletti, S.; Rossini, C.; Duse, S.; Docchio, F.; Pasinetti, S.; Zambonardi, F.; Semeraro, F.; Sansoni, G.; Rosei, C. Agabiti; Pileri, P.; et al.
Abstract : Objective: The evaluation of the morphological characteristics of small resistance arteries in human beings in not easy. The gold standard is generally considered to be the evaluation of the media to lumen ratio of subcutaneous small vessels obtained by local biopsies and measured by wire or pressure micromyiography. However, non-invasive techniques for the evaluation of retinal arterioles were recently proposed, in particular two approaches seem to provide interesting information: scanning laser Doppler flowmetry and adaptive optics; both of them provide an estimation of the wall to lumen ratio (WLR) of retinal arterioles. The reproducibility of such measurements was previously stated to be acceptable (coefficient of variation <10% for SLDF, <4% for RTX-1), however, no direct comparison of the two techniques in the same population was previously performed. Design and method: Therefore, we evaluated 18 subjects and patients (10 normotensives, 8 hypertensives, 7/18 severely obese). In all of them an evaluation of the WLR of retinal arterioles was made by Scanning Laser Doppler Flowmetry (SLDF, Heidelberg Engineering, Heidelberg, Germany) and adaptive optics (RTX-1, Imagine Eyes, Orsay, France). The same operator evaluated the same acquired images in two different days (intra-observer variability), and two different operators evaluated the same images in the same day (inter-observer variability). Results: The results are reported in the Table (***p < 0.001). Variation coefficient of SLDF is much greater than that of AO. Figure. No caption available. Conclusions: It is clear how the reproducibility of the evaluation of the WLR with adaptive optics is far better, as compared with SLDF, since the variation coefficient are clearly lower. This may be important in terms of clinical evaluation of microvascular morphology in a clinical setting.